Electric impedance tomography for monitoring volume and size of the urinary bladder - Leonhardt, Steffen; Cordes, Axel; Plewa, Harry; Pikkemaat, Robert; Soljanik, Irina; Möhring, Klaus; Gerner, Hans-Jürgen; Rupp, Rüdiger (Biomedical engineering, 2011)
A novel non-invasive technique for monitoring fluid content in the human bladder is described. Specifically, a precommercial electric impedance tomograph (EIT) was applied to measure and visualize impedance changes in the lower torso due to changes in bladder volume. Preliminary measurements were conducted during routine urodynamic tests of nine male paraplegic patients, in whom a contrast agent was slowly infused into the bladder for diagnostic purposes. In some patients, a good correlation between bladder volume and EIT measurements was found, whereas in others the correlation was still good but inverted, presumably due to a poor electrode positioning. These preliminary results indicate that a sufficiently accurate finite element modeling of the impedance distribution in the abdomen, and proper electrode positioning aids, are important prerequisites to enable this technology to be used for routine measurement of bladder volume.
Gesehen am 17.08.2022